Biopriming of cucumber seeds using actinobacterial formulas as a novel protection strategy against Botrytis cinerea - Jurado, Macarena M.; Suárez-Estrella, Francisca; Toribio, Ana J.; Martínez-Gallardo, María R.; Estrella-González, María J.; López-González, Juan A.; López, María J. (Frontiers in Sustainable Food Systems, 2023)
This work highlights the ability of various actinobacterial formulas, to control the incidence of grey-mold caused by Botrytis cinerea in cucumber seedlings. Protocols applied aimed at the preliminary characterization of the actinobacterial collection and the biopolymers used as carriers were very useful for predicting their phytotoxic, phytostimulating and biopesticidal capacity. First, the phytostimulatory or phytotoxic potential of 3 biopolymers at 3 different concentrations and a collection of 10 actinobacteria were analyzed by calculating the germination index in cucumber seeds by seed dipping (biopriming). In general, two-member consortia and independent actinobacteria previously selected reached a phytostimulant effect on cucumber seedlings after their application by biopriming. Likewise, the selected actinobacteria were characterized, sole and in co-cultures, according to its ability to inhibit the growth of B. cinerea by dual culture bioassays. Finally, after selecting the most effective actinobacterial formulas, a preventive grey-mold bioassay was performed based on cucumber seed biopriming. The strain A5 and A7, in axenic and co-culture, showed to be the most efficient strains against the in vitro growth of B. cinerea. Seed biopriming strategy with actinobacterial formulas revealed a remarkable promoter effect in the early stages of plant development and after the infection with the phytopathogen fungus was remained. Definitely, the microbial formulas used in this work showed a phytostimulant and biopesticide character, laying the foundations for subsequent studies that allow a deeper scrutiny of the mechanisms of action that grant the specialization of the effect that occurs between beneficial microorganisms and specific plant hosts.